Brazilian Protocol for Sexually Transmitted Infections, 2020: infections that cause cervicitis - Miranda, Angélica Espinosa (Rev Soc Bras Med Trop, 2021)
Infections that cause cervicitis are a topic presented in the "Clinical Protocol and Therapeutic Guidelines for Comprehensive Care for People with Sexually Transmitted Infections", published by the Brazilian Ministry of Health in 2020. The document was developed based on scientific evidence and validated in discussions with experts. This article presents epidemiological and clinical aspects of infections that cause cervicitis and recommendations on screening, diagnosis, and treatment of affected people and their sexual partnerships. Also, it discusses strategies for surveillance, prevention, and control of these infections for health professionals and health service managers involved in the programmatic and operational management of sexually transmitted infections. Expanding access to diagnostic tests and early treatment are crucial for controlling the spread of pathogens that cause cervicitis.